Towards a complete description for individual course units: a follow-up to the Bologna proposals - Barros, João Paulo (2013)
The ECTS User's Guide prescribes the use of learning outcomes in the description of individual course units and states the need to specify the associated assessment criteria. Here, we present a concrete template proposal for the description of individual course units that adds two additional alignments to the well-known double alignment strategy. More specifically, we propose the specification of four alignments: learning outcomes to contents; learning outcomes to assessment; assessment to the teaching and learning strategies; and assessment to grading. To support the latter, a specific grading strategy is briefly presented. Additionally, learning outcomes are classified according to the European Qualification Framework for Lifelong Learning.